Pengembangan Model Passing untuk Meningkatkan Keterampilan Permainan Bola Voli - Ahmad Alwi; Dicky Reva Apriana Sanga Dwi (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to develop a model of passing practice that can improve volleyball game skills in elementary school students. This study uses a quantitative approach with an experimental method. The instrument used was a test of upper and lower passing skills within 60 seconds. Data analysis techniques include normality tests, homogeneity tests, and hypothesis tests. The sample in this study consisted of grade V students in one of the randomly selected elementary schools. The passing training model applied is a pair exercise with a distance of 10 meters, carried out routinely for three weeks with a frequency of three times a week. Each session lasts 40 minutes and is carried out under the supervision of a physical education teacher. The focus of the exercise is directed at improving the basic techniques of upper and lower passing which are gradually and pleasantly developed to suit the developmental characteristics of elementary school students. The results showed that the consistent application of the paired passing exercise model was able to improve the accuracy, coordination, and strength of students' arm muscles. In addition, it was found that there was an increase in student motivation and active participation in volleyball learning activities. This exercise model also creates a more interactive learning atmosphere and encourages students to work together, resulting in collaborative and meaningful learning. These findings prove that the use of a training model that is systematic, fun, and in accordance with the characteristics of learners can significantly improve the basic skills of the game of volleyball. This exercise has proven to be effective and can be used as an alternative learning method in physical education in elementary school. It is recommended that physical education teachers consider integrating this exercise model into the learning program so that student learning outcomes in volleyball can be more optimal and sustainable.